Newsworld - Pierce, Todd James, 1965- (Book collections on Project MUSE., 2006)
News is "one of the few things that connects us as a nation" observes the protagonist in the title story of Newsworld, a new collection by Todd James Pierce that explores America's obsession with news and entertainment culture. The characters in "Newsworld" seek to design realistic theme park attractions, such "OJ's Bronco: The Ride" and "Siege at Waco," that allow park guests to experience the complexities of contemporary news events for themselves. In the story "Columbine: The Musical," high school students stage a musical written as a means of discussing school violence, while their vice p.